P079 Building quality improvement capacity for rheumatology: outcomes from the first BSR national workshop. (23rd April 2022) - Sharp, Charlotte A; Benson, Rosalind; Baird, Hannah; MacPhie, Elizabeth
Abstract: Background/Aims: Quality improvement (QI) is now an expected part of healthcare professional practice. After identifying a gap in available training and successfully delivering a QI course for 35 clinicians at the Northwest Rheumatology Club, trainee representatives were invited by the BSR invited to convene a national workshop. Methods: The first BSR Quality Improvement Practical Methodology Workshop was held in March 2021 (online, due to COVID-19). Materials were adapted from the well-established Trainees Improving Patient Safety through Quality Improvement (TIPSQI) initiative. Plenaries covered the Model for Improvement, process mapping, SMART aims, driver diagrams, stakeholder engagement, illustrated using rheumatology-specific case-studies. Delegates (with mixed experience / professional role) practiced using tools in small, facilitated, breakout rooms. Pre-course surveys informed course design. Post-course and six-month follow up surveys evaluated impact. Because there are no validated tools to evaluate the impact of QI training, Kirkpatrick's four-step hierarchical model, commonly used in this context, was employed. Results: Of 30 delegates (consultants, trainees, pharmacists, nurses, physiotherapists), 28, 22 and 4 completed pre-course, post-course and six-month surveys, respectively (Table 1 ). For Kirkpatrick level 1, 'reaction', all respondents were 'satisfied', with 100% recommending to colleagues. Using driver diagrams as an exemplar to evaluate level 2, 'learning', pre-course, delegates were: not aware 16/28(57.1%), aware 9/28(32.1%), confident to use 3/28(10.1%), 0/29(0%) confident to teach. Post-course improvements showed confidence to use 22/22(100%), and teach 12/22(54.6%) (maintained at six months). Given low numbers of six-month respondents, assessing long-term impact is challenging. Evaluating level 3, 'behaviour', all 4/4(100%) respondents conducted QI post-course, with 2/4(50%) teaching. Delegates reported that the course gave confidence to use tools and support others. In evaluating level 4, 'results', 1/4(25%) felt the course had changed the impact of their work, with 3/4(75%) reporting time and institutional constraints as barriers to conducting QI. Conclusion: The QI course has been commissioned as a BSR annual 'core educational' offering, with feedback showing it was needed, wanted, and effective in delivering core QI principles. In response to six-month feedback, additional post-course-support is planned in future, aiming to capacity build expertise in QI and embed a sustainable culture of improvement across the rheumatology community. Disclosure: C.A. Sharp: None. R. Benson: None. H. Baird: None. E. MacPhie: Other; EM is the North West Rheumatology Club secretary and meetings have been sponsored by MSD, UCB, Abbvie and Lilly.